Lack of MDM2 interpretation guidelines contribute to diagnostic difficulty in a case of undifferentiated sarcoma - Melissa M. Straub; Ferrin C. Wheeler; Sarah M. Deraney; Emily S. Reisenbichler (Elsevier, 2018)
Undifferentiated sarcomas are malignant mesenchymal neoplasms lacking any specific line of differentiation and are typically a diagnosis of exclusion requiring supplemental diagnostic testing. We present a case of a 68 year old male with a thigh mass. Microscopic evaluation revealed a spindle and epithelioid cell neoplasm with pleomorphic nuclei arranged in vague, irregular fascicles and positive nuclear MDM2 staining. Fluorescence in situ hybridization (FISH) analysis demonstrated 36.2 average MDM2 signals and 31.7 average centromere 12 signals per cell (1.1 ratio). Although a dedifferentiated liposarcoma is defined by MDM2 amplification, the lack of an adjacent well differentiated liposarcoma component and radiographic characteristics argued against a lipomatous tumor in this case, leading to a diagnosis of undifferentiated sarcoma, despite the markedly increased MDM2 copy number. With expanding utilization of molecular and cytogenetic testing of tumors, this case highlights questions regarding the interpretation and incorporation of these results in diagnostic soft tissue pathology. Keywords: Undifferentiated pleomorphic sarcoma, MDM2, Fluorescence in situ hybridization (FISH), Polysomy